Pelaksanaan Gerakan Literasi Sekolah Dalam Menumbuhkembangkan Karakter Siswa di Sekolah Dasar - Dewi Lestari, Riska (PKBM DAARUL AHKAAM, 2025)
This research aims to describe the implementation of the School Literacy Movement and the impact of the implementation of the School Literacy Movement in developing the character of students at SD Negeri Rejosari 1, Kawedanan District, Magetan Regency. This research uses a qualitative research approach with a case study method. Data sources in this research are school principals, class teachers, library staff, students, and documents. Sampling in this qualitative research used purposive sampling techniques and the data collection techniques used were observation, interviews, document studies and questionnaires. The validity test used source triangulation and technique triangulation and was analyzed using the Miles and Huberman model of qualitative descriptive analysis. The research results show that the school literacy movement in this research was implemented through 3 stages, namely: habituation stage, development stage, and learning stage. The implementation of the school literacy movement has a positive impact on student learning achievement which shows that students' attitudes towards the character values ​​of the literate ecosystem in class IV and class V reach a very high percentage; on knowledge in the form of Indonesian language learning results seen from the percentage of completeness and the class average shows that Indonesian language learning results have experienced a very small increase; Meanwhile, students' skills in portfolio activities include literacy skills in the form of reading, gathering information and writing. The ability to write in a student's portfolio shows mastery of the levels of beginning writer, youth writer and intermediate writer.